Insight into the early hydration characteristics of Portland cement with hydroxyethyl methyl cellulose highlighted by 1H low-field NMR - Wang, Shunxiang; Zhang, Guofang; Liang, Chaofeng; Huang, Tianyong; Zhang, Peng (Construction & building materials, 2024)
1H low-field nuclear magnetic resonance (1H NMR) as a non-destructive test method can effectively capture the water state changes in cement pastes. The water changes can in turn reflect the early hydration characteristics of cement pastes. Hydroxyethyl methyl cellulose (HEMC) with different viscosities affects the hydration characteristics of cement by acting on the water in different states. The following experimental results are obtained by testing hydration of cement pastes with HEMC by using 1H NMR test. Incorporating 0.1–3% HEMC with different viscosities all can effectively control the bleeding water phenomenon. HEMC can absorb a part of the water in the cement pastes. Incorporating 2–3% HEMC significantly delays the enrichment of the gel pores water and interlayer water. When the content of HEMC increases from 0% to 3%, the hydration degree of cement pastes tends to decrease. Besides, HEMC with higher viscosity of 15000–40000 mPa·s obviously delays the hydration process of cement pastes compared to HEMC with lower viscosity of 400 mPa·s. [Display omitted] •1H low-field NMR can efficiently detect the hydration process of Portland cement with hydroxyethyl methyl cellulose (HEMC).•Incorporating HEMC effectively controls the bleeding water phenomenon.•The early cement hydration is obviously delayed by incorporating HEMC.•HEMC with higher viscosity more significantly affects the early hydration.